SHAPING PERCEPTIONS IN THE ARCTIC: THE ROLE OF NARRATIVE AND INFLUENCE IN A CONTESTED REGION - Adam Lajeunesse (The Journal of Intelligence, Conflict and Warfare)
On November 20, 2024, Dr. Adam Lajeunesse presented Shaping Perceptions in the Arctic: The Role of Narrative and Influence in a Contested Region for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed included China’s Arctic narrative, evolution of Chinese narratives in the Arctic and the Chinese-Russian cooperation.